Integrasi nilai Pancasila dalam pendidikan karakter: Strategi menghadapi tantangan globalisasi - Agus, Andi Aco (Rayhan Intermedia, 2025)
Pancasila-Based Character Education is Very Important Because It is the Main Fortress in Maintaining National Identity in the Midst of Globalization, Without Pancasila Values, Young Generation Will Be Easily Influenced by Instant Culture, Hedonism, and Individualism Which Can Weaken the Spirit of Nationalism Character Education Functions as a Filter, So That the Young Generation Remains Critical in Absorbing Foreign Culture, But Does Not Lose Their Identity. Strategy for Integrating Pancasila Values ​​in the Curriculum, Educator Exemplary, Conducive School Environment, Utilization of Digital Technology, Strengthening Extracurricular Activities, Local-Based Approaches, and Contextual, The Challenges: Weak Role Models, Low Supervision of Foreign Cultural Dominance in Digital Media. Solutions That Can Be Done Are: Strengthening Synergy Between Schools, Families and Communities in Instilling Character Values, and Increasing the Role of the Government in Making Supporting Policies..